2013
DOI: 10.1159/000363730
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of the in vitro Antistaphylococcal Effect of Oxacillin and Tetracycline by the Anti-Inflammatory Drug Diacetyl Rhein

Abstract: Background: The anti-inflammatory drug diacetyl rhein has been found to possess promising antistaphylococcal effects against various drug-resistant strains in our previous study. In the present work, we explored the in vitro combinatory interactions of diacetyl rhein with oxacillin and tetracycline against 13 standard strains and clinical isolates of Staphylococcus aureus, including those resistant to erythromycin, methicillin and tetracycline. Methods: Minimum inhibitory concentrations were determined by brot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…as laxative (Bruneton, 1999) and antiinflammatory agents (Nguon et al, 2014). In addition, our previous study demonstrated that redox potential alone could not fully explain all aspects of pharmacological action of quinones (Landa et al, 2012).…”
Section: Resultsmentioning
confidence: 96%
“…as laxative (Bruneton, 1999) and antiinflammatory agents (Nguon et al, 2014). In addition, our previous study demonstrated that redox potential alone could not fully explain all aspects of pharmacological action of quinones (Landa et al, 2012).…”
Section: Resultsmentioning
confidence: 96%
“…Despite a previous in vitro study describing promising growth-inhibitory effects of diacerein against various drug-resistant staphylococcal strains (19), the synergistic anti-Staphylococcus aureus effects of its active metabolite rhein with ampicillin and oxacillin were also discovered (20). No data have reported the results of the use diacerein against Gram-positive bacteria in ophthalmology or against strains such as Enterococcus spp., Staphylococcus intermedius, Staphylococcus haemolyticus, Staphylococcus xylosus, Staphylococcus hominis, and Staphylococcus capitis.…”
Section: Effect Of Diacerein Eye Drop On Treatment Of Staphylococcus mentioning
confidence: 98%
“…It works by blocking the actions of interleukin-1 beta, a protein involved in inflammation. A previous in vitro study showed that diacerein has growth-inhibitory effects against various drug-resistant staphylococcal strains, and synergistic or additive effects with oxacillin and tetracycline were observed against all Staphylococcus aureus strains (19,20). To date, there are no reports describing the therapeutic effect of diacerein for the treatment of bacterial keratitis.…”
mentioning
confidence: 99%
“…Combined drug sensitivity results. Prior research has suggested that diacerein can enhance the antibacterial effect of oxacillin on Staphylococcus aureus in vitro [15] . In this study, the combined drug sensitivity test of four β-lactam drugs and diacerein was carried out for MRSE, and FIC values was shown in Table 3.…”
Section: Content Of Ros In Bacteriamentioning
confidence: 99%